Analysis of the Effect Liquidity and Solvability to Profitability (Case Study of Coal Mining Sub-Sector Companies Listed in Indonesia Stock Exchange) - Setyawan, Ryand Daddy; Fauzi, Padlun (Journal Of Accounting Management Business And International Research, 2023)
The purpose of this study was to determine the effect of liquidity and solvability on profitability in the Coal Mining Sub-Sector Companies listed on the Indonesia Stock Exchange period 2017-2022. This research method uses a quantitative approach with multiple regression analysis. The source of this research uses secondary data sourced from the financial statements of the Coal Mining Sub-Sector Company listed on the Indonesia Stock Exchange. The sample of this study was 15 with Benjamin Graham’s strategy elimintaion companies using Purposive Sampling techniques. The results of this study indicate that partially liquidity has a significant effect on profitability and solvability has a significant effect on profitability. Simultaneously the results obtained that Liquidity, Solvability and Asset Growth significantly influence Profitability. Determination coefficient value of 0,33 shows that Liquidity and Solvability provide diversity of 33% on profitability, while the remaining 67% is influenced by other factors not observed in this study.